The Conceptual Model of Improving The Perfomance of Madrasah Teachers - Liana Ariesha Khoerudin; Siti Qomariyah; Hani Sanjaya; Pepen Supendi (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
This article examines the role of leadership style in improving teacher performance at MTs Al Matuq Sukabumi. Leadership is defined as the overall action to influence and move people, in a joint effort to achieve goals, or a more complete definition can be said that leadership is an organized process of giving way in a formal organization, to achieve the goals that have been set. This research uses a descriptive qualitative approach. This research site is located at MTs Al Matuq Sukabumi. Data collection techniques that researchers use are observation and interviews. The results of the study show that the head of MTs Al Matuq has the competency as the head of the madrasah and is able to implement the madrasah programs that have been planned. Therefore, forming an effective and efficient climate, madrasah culture and teacher job satisfaction. This has implications for the high involvement and participation of MTs Al Matuq teachers in making organizational decisions for their educational institution. Instilled in the teacher of MTs Al Matuq psychologically sided with his work and considers his performance as his self-esteem too at the same time. Artikel ini mengkaji tentang peran gaya kepemimpinan dalam meningkatkan kinerja guru di MTs Al Matuq Sukabumi. Kepemimpinan didefinisikan sebagai keseluruhan tindakan untuk mempengaruhi dan menggerakkan orang-orang, dalam usaha bersama untuk mencapai tujuan, atau definisi lebih lengkapnya dapat dikatakan bahwa kepemimpinan adalah proses pemberian jalan yang terorganisir dalam sebuah organisasi formal, untuk mencapai tujuan yang telah ditetapkan. Penelitian ini menggunakan pendekatan kualitatif jenis deskriptif. Situs penelitian ini berada di MTs Al Matuq Sukabumi. Teknik pengumpulan data yang peneliti gunakan yaitu obserasi dan wawancara. Hasil penelitian menunjukan bahwa kepala MTs Al Matuq memiliki kompetensi sebagai kepala madrasah dan mampu mengimplementasikan program-program madrasah yang telah di rencanakan. Sehingga, membentuk iklim, budaya madrasah dan kepuasan kerja guru yang efektif dan efisien. Hal ini berimplikasi pada keterlibatan dan partisipasi yang tinggi dari para guru MTs Al Matuq dalam ikut mengambil keputusan organisasi lembaga pendidikannya itu. Tertanam pada diri guru MTs Al Matuq memihak secara psikologis terhadap pekerjaannya dan menganggap kinerjanya adalah sebagai harga dirinya juga sekaligus.